PENGARUH CITRA DESTINASI TERHADAP KEPUASAN WISATAWAN DI ANJUNGAN DAERAH SUMATERA SELATAN TMII - Taufiq Kurniawan; Maharani Mustika Ayu (Bogor Hospitality Journal, 2021)
The purpose of this study was to determine the effect of destination image on tourist satisfaction at the South Sumatran Pavilion, Taman Mini Indonesia Indah. This research method uses a quantitative research approach with purposive sampling technique and a total sample of 100 respondents. The data analysis method used is Structural Equation Modeling (SEM) analysis with destination image as the independent variable and tourist satisfaction with the dependent variable. The independent variables used consist of Cognitive Image, Unique Image and Affective Image dimensions.Based on the results of the study, it was concluded that there was a significant influence between the destination image simultaneously on tourist satisfaction at the South Sumatra Regional Pavilion at Taman Mini Indonesia Indah. This can be seen from the p-value which is greater than 0.05, which is 0.092. The dimension that gives the biggest contribution is the Cognitive Image dimension, with a load factor value of 0.64. The relationship between the Cognitive Image dimension and its indicators shows that the employee's indicator of being able to convey information about the bridge well gives the largest contribution to the Cognitive Image dimension with a load factor value of 0.95.